(untitled) (2013)
Deterioration models allow predicting pavement condition and the development of maintenance programs. Normally, when evaluating pavement performance through model deterioration, the forecast given is a determinist value. However, pavement engineering projects have a degree of uncertainty. This implies that an adequate performance of the engineering solution cannot be absolutely guaranteed. The aim of this research is to incorporate probability in the output of a structural cracking model. To achieve this objective the model of crack initiation and progression of HDM-4 was used several scenarios defined based on geographic location, type of traffic and structural capacity of Chilean roads. To incorporate probability in the structural cracking models, a simulation model that reproduced the deterioration due to cracking for a lifecycle of 25 years was developed, based on random variables input. With the set of outputs of the simulation, probability density functions that represent the probabilistic response of the deterioration model were developed. These probability density functions represent the cracking initiation and cracking progression of all structural cracks and wide cracks of 14 groups of Chilean roads. Although the research was carried out using Chilean data, the methodology presented could be applied to other states or countries.